Ice thickness from low-frequency radar profiling at Djupranen and Leningradkollen ice rises, East Antarctica - Lindbäck, Katrin (Norwegian Polar Institute, 2020)
The dataset consists of ice thickness derived from low-frequency radar measurements on Djupranen and Leningradkollen ice rises, Dronning Maud Land (70 deg S, 12 deg E). Processing methods are described in the peer-reviewed paper Lindbäck et al., 2019 (https://doi.org/10.5194/tc-2019-108). If you use the dataset in presentations and publications please also refer to this data portal reference (authors and doi). The dataset will be updated when the quality of the data is improved or if new datasets become available. File format: Text file Contact person: Kenichi Matsuoka (kenichi.matsuoka@npolar.no) This work was part of the MADICE (Mass balance, dynamics, and climate of the central Dronning Maud Land coast, East Antarctica) project co-led by the Norwegian Polar Institute in Norway and National Centre for Polar and Ocean Research in India (https://www.npolar.no/prosjekter/madice/).